Predictors and outcomes of cardiac arrest in the emergency department and in-patient settings in the United States (2016–2018). (January 2022) - Mir, Tanveer; Qureshi, Waqas T.; Uddin, Mohammed; Soubani, Ayman; Saydain, Ghulam; Rab, Tanveer; Kakouros, Nikolaos
Graphical abstract: Abstract: Background: Outcomes of cardiac arrest (CA) remain dismal despite therapeutic advances. Literature is limited regarding outcomes of CA in emergency departments (ED). Objective: To study the possible causes, predictors, and outcomes of CA in ED and in-patient settings throughout the United States (US). Methods: Data from the US national emergency department sample (NEDS) was analyzed for the episodes of CA for 2016–2018. In-hospital CA was divided into in-patient (IPCA) and in the ED (EDCA). Only patients who had cardiopulmonary resuscitation (CPR) within the hospital were included in the study (out-of-hospital were excluded). Results: A total of 1, 068, 847 CA (mean age 63.7 ± 19.4 years, 24%females), of whom 325, 062 (30.4%) EDCA and 177, 104 (16.6%) IPCA were included in the study. Patients without CPR, 743, 785 (69.6%), were excluded. Survival was higher among IPCA 55, 821 (31.6%) than the EDCA 32, 516 (10%). IPCA encounters had multifactorial associated etiologies including respiratory failure (73%), acidosis (38.7%) sepsis (36.8%) and ST-elevated myocardial infarction (STEMI) (7.3%). Majority of ED arrests (67.1%) had no possible identifiable cause. The predominant known causes include intoxication (7.5%), trauma (6.4%), respiratory failure (5%), and STEMI (2.7%). Cardiovascular interventions had significant survival benefits in IPCA on univariate logistic regression after coarsened exact matching for comorbidities. IPCA had higher intervention rates than EDCA. For all live discharges, a total of 40% of patients were discharged to hospice. Conclusion: Survival remains dismal among CA patients especially those occurring in the ED. Given that there are considerable variations in the etiology between the two studied cohorts, more research is required to improve the understanding of these factors, which may improve survival outcomes.